2013
DOI: 10.1039/c3sc51993g
|View full text |Cite
|
Sign up to set email alerts
|

Pd(ii)-catalyzed alkoxylation of unactivated C(sp3)–H and C(sp2)–H bonds using a removable directing group: efficient synthesis of alkyl ethers

Abstract: The Pd(II)-catalyzed alkoxylation of unactivated C(sp 3 )-H and C(sp 2 )-H bonds using a new bidentate directing group has been developed. Alkoxylation occurs selectively at the b position with broad substrate scope and high tolerance of functional groups (chloro, cyano, ether, ester, olefin, amino, etc.). Besides alkoxylation of the b-C-H bonds, g-alkoxylation of C(sp 2 )-H bonds could also be achieved, provided that no reactive b-C-H bonds were present. In addition, this DG is readily available and removable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 291 publications
(80 citation statements)
references
References 74 publications
1
77
1
1
Order By: Relevance
“…[5] During the course of our investigations, we found that when KBrO 3 was used as the oxidant, the phenylalanine derivative 2 a was transformed into a-amino-b-lactam 3 a in 16 % yield, presumably through intramolecular C(sp 3 ) À H amidation of the methylene group [Eq. (2) (Phth = phthaloyl)].…”
mentioning
confidence: 99%
“…[5] During the course of our investigations, we found that when KBrO 3 was used as the oxidant, the phenylalanine derivative 2 a was transformed into a-amino-b-lactam 3 a in 16 % yield, presumably through intramolecular C(sp 3 ) À H amidation of the methylene group [Eq. (2) (Phth = phthaloyl)].…”
mentioning
confidence: 99%
“…The direct oxidation of simple arenes is an attractive process to obtain phenols, which have many applicationsi no rganic synthesis. [6,7] The palladium-catalyzed CÀHa cetoxylation of benzene has been described in the presence of strong oxidants (e.g.,K 2 Cr 2 O 7 ,K 2 S 2 O 8 ), [8] albeit with low catalytic turnover and significant formationo ft he biphenyl byproduct. In 1996, Crabtree reported the use of PhI(OAc) 2 as an oxidant, andi t showedhigher activity and precluded the formation of biphenyl.…”
mentioning
confidence: 99%
“…[13] Consequently, there is tremendous interest in the synthesis of nonproteinogenic a-amino acids. [14] As part of our efforts to synthesize biologically important organic molecules by direct C(sp 3 )ÀH functionalization, [15] we envisioned that b-alkyl-a-amino acids could be accessed by the alkylation of the b-methylene CÀH bonds of simple a-amino acid derivatives. [16] However, this reaction was rather challenging because of the low reactivity of methylene C(sp 3 ) À H bonds and the tendency of metal alkyl intermediates to undergo side reactions.…”
mentioning
confidence: 99%